Interactions of milk proteins with low and high acyl gellan: Effect on microstructure and textural properties of acidified milk. (October 2016) - Buldo, Patrizia; Benfeldt, Connie; Carey, Juan Pablo; Folkenberg, Ditte Marie; Jensen, Hanne Bak; Sieuwerts, Sander; Vlachvei, Kalliopi; Ipsen, Richard
Abstract: The effect of addition of low and high acyl gellan (LAG/HAG) at three different concentrations on the microstructure and texture of acidified milk systems with different casein to whey protein ratios was investigated. The systems with added LAG exhibited a continuous gel network whereas micro-phase separation occurred when HAG was added. The continuous gel network was indicative of complexation between the polysaccharides and casein, which in turn led to enhanced textural properties and reduced syneresis. Those properties were reduced by decreasing the casein to whey protein ratio as fewer complexes were formed. HAG appeared to be incompatible with casein micelles, which resulted in a micro-phase separated system. This caused decreased textural properties but a higher physical stability due to HAG present in the serum phase available to bind water. By decreasing the casein to whey protein ratio the textural properties were improved at expense of the physical stability, indicating a preferential binding between HAG and whey proteins. Graphical abstract: Highlights: LAG formed complexes with casein. Complex formation between LAG and casein led to enhanced textural properties. HAG was incompatible with casein and had a preferential binding for whey proteins. Incompatibility between biopolymers led to enhanced physical stability.